2018
DOI: 10.1108/aaaj-04-2015-2023
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the quality of corporate environmental reporting

Abstract: Purpose The purpose of this paper is to provide a multidimensional model for assessing the quality of corporate environmental reporting (CER) incorporating both preparer- and user-based views. Design/methodology/approach As opposed to frequently used researcher-chosen proxies, the authors used an online questionnaire asking preparers and users how they assess the quality of a company’s environmental report. Findings The analysis of the responses of 177 users and 86 preparers shows that quantity was not per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 63 publications
(290 reference statements)
2
100
0
3
Order By: Relevance
“…Prior empirical studies indicate that CESD is influenced by the level of environmental risk of companies (i.e. sensitivity to the environment) (Brammer and Pavelin, ; Helfaya, ; Tauringana and Chithambo, ). Thus, we re‐run Equation by splitting our sample into high environmentally sensitive industries (HESI) and low environmentally sensitive industries (LESI).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior empirical studies indicate that CESD is influenced by the level of environmental risk of companies (i.e. sensitivity to the environment) (Brammer and Pavelin, ; Helfaya, ; Tauringana and Chithambo, ). Thus, we re‐run Equation by splitting our sample into high environmentally sensitive industries (HESI) and low environmentally sensitive industries (LESI).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the quality of CESD (QUAL_ED), we used a less subjective multi‐dimensional quality model (MQM) developed by Helfaya () for assessing the quality of environmental discourse. This MQM goes beyond the more traditional author‐based disclosure indices, focusing on a preparer‐ and user‐based index that assesses the quantity of CESD and captures a high level of content, credibility and communication of environmental information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diouf and Boiral [11] showed that SRQ is perceived by stakeholders as correlated to different dimensions such as balance and clarity of information. Further, by adopting the perspective of both users and preparers, Helfaya et al [12] showed that quality is a multidimensional concept that cannot be understood by measuring only the quantity of disclosed information. These researchers confirmed many important scientific contributions [13][14][15][16][17][18], despite other studies having found a significant correlation between quantitative and qualitative measures of SRQ [19].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have consistently developed different metrics and instruments to measure SRQ, most of which are based on a compounded approach and on content analysis [12,[19][20][21][22][23][24][25]. According to Helfaya et al [12] (p. 18) quantity can be considered a secondary factor of quality because the most important determinants concern the content of the reports and are related to aspects of sustainability reporting such as information type, adoption of guidelines, and inclusion of quantitative or financial measures of social and/or environmental performance.…”
Section: Introductionmentioning
confidence: 99%